Industrial policy for CARICOM - Pantin, Dennis A. ([CCS] GeorgetownGY, 1996)
Addresses the issue of the theoretical and empirical case for industrial policy. Reviews the experience with industrial (development) policy in CARICOM betwween 1945-1996. Analyses the changes in the international trade-related environment as the necessary context for CARICOM industrial policy in the 1990s. Advances proposals for a CARICOM industrial policy including transitional arrangements.